The US-India nuclear pact policy, process, and great power politics - Pant, Harsh V. (New Delhi ; Oxford : Oxford University Press, 2011)
This text examines the factors that were instrumental in making the US-India nuclear agreement. It underlines a range of factors at the structural, domestic, political and individual level that helped shape the recent trajectory of US-India relationship and made the nuclear pact possible.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Nuclear nonproliferation -- India; Nuclear nonproliferation -- United States; India -- Foreign relations -- United States; United States -- Foreign relations -- India